Course Title: ENGLISH MORPHOLOGY For first year LMD students - Alexandra Smirnova (Blida2- Faculty of Art and Languages, 2025)
Morphology is a branch of grammar that studies the internal structure of words, word formation processes, as well as word forms that appear in different grammatical contexts. Most words are complex structures that can be divided further into smaller meaningful units called morphemes. The combination of morphemes is not a random process, rather it is governed by combinatorial rules that ensure the systematicity of word forms and word formation processes. To become a proficient speaker of English, it is essential therefore to be aware of typical combinatorial patterns in morphology in order to be able to use words and their forms correctly in different grammatical contexts. The course ‘English Morphology’ will introduce students to the internal structure of English words. Upon the completion of the course, students will be able to recognize typical combinatorial patterns of English morphemes and use them as building blocks in their speech and writing.
Keywords: ENGLISH MORPHOLOGY; Syllabus; Grammar